2021
DOI: 10.47836/pjst.29.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Revisited the Critical Load Assessment of Huang et al. on Willems Tested Beck Column

Abstract: Dynamic stability of elastic structures is a fascinating topic. Many researchers have examined the problem theoretically considering a cantilever column under a tip-concentrated tangential load, the so-called Beck column. Experimental verification is demanded since the critical load of Beck column is found to be approximately eight times to that of the classical Euler column. Different types of testing procedures are being adopted to create the follower force. Among them, notable Willems experimentation provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Though the configuration has a critical load close to Beck's problem, theoretical analysis of Huang et al (1967) and discussion of Augusti et al (1967) have concluded that Willems test results are not representing the Beck column. Praveen et al (2021) have revisited the critical load assessment of Huang et al (1967) and corrected the error in the computed values and confirmed the adequacy of Willems's (1966) approach on the Beck column. Xiong et al (1989) have considered a centripetally loaded model and simulated Beck's column showing equivalence of the first and second modes individually, whereas Praveen et al (2020) have demonstrated the equivalence of the first and second modes directly from the dynamic characteristics of the Beck column.…”
Section: Introductionmentioning
confidence: 79%
“…Though the configuration has a critical load close to Beck's problem, theoretical analysis of Huang et al (1967) and discussion of Augusti et al (1967) have concluded that Willems test results are not representing the Beck column. Praveen et al (2021) have revisited the critical load assessment of Huang et al (1967) and corrected the error in the computed values and confirmed the adequacy of Willems's (1966) approach on the Beck column. Xiong et al (1989) have considered a centripetally loaded model and simulated Beck's column showing equivalence of the first and second modes individually, whereas Praveen et al (2020) have demonstrated the equivalence of the first and second modes directly from the dynamic characteristics of the Beck column.…”
Section: Introductionmentioning
confidence: 79%